Investigating multiple fan beam projection technique using optical fibre sensor in process tomography - Abdul Rahim, Ruzairi (Penerbit UTM Press, 2007)
This paper investigates the acquisition rate for a multi-projection technique using optical fibre sensors for a fan beam optical tomography system. The multi-projection technique allows more than one emitter to project light at the same time. For the 32 pairs of sensors used, the 2-projection technique is being investigated whereby 16 sets of projections will complete one frame of light emission. Compared to the conventional single light projection technique used in switch-mode fan beam, multiple light projections technique has shown to be able to achieve a higher data acquisition rate